Aristotle and the ERA: Measuring the immeasurable - Bennett, Dawn; Franzmann, Majella (SAGE publishing, 2013)
The research assessment framework is an unstable reality in many countries. While few would disagree that there is a need to measure and reward research excellence, there has been little investigation of how assessment mechanisms relate to knowledge itself. With a focus on the arts and humanities and writing from an Australian perspective, this paper draws together discussions of research assessment frameworks and forms of knowledge to consider what can and cannot be measured, and what we might gain from (or lose from not) measuring these things. We argue that the focus on measurable outputs risks a culture that favours effective packages of knowledge at the same time as ignoring the immeasurable, or hidden elements of research and scholarship – elements that Aristotle considered to underpin scholarship itself.